Dual Curriculum Integration Strategy to Address Rest Time Deficit and Circadian Disturbances in Students - Husen Iskandar (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The implementation of a dual curriculum in Islamic boarding schools that integrates national standards and local religious content is often carried out without an adequate synchronization process, thus triggering an accumulation of learning loads that exceed the capacity of biology students. This phenomenon has an impact on the creation of a very dense daily schedule structure for 24 hours, which systematically results in a chronic sleep deficit and disruption of circadian rhythms in students. This policy research aims to outline a curriculum integration strategy to restore the quality of physical and cognitive health of students through a more humane educational management approach. The policy methodology used is a qualitative descriptive analysis with a literature study approach and a curriculum workload audit to identify material redundancy and inefficiencies in the flow of daily activities in Islamic boarding schools. Using root cause analysis techniques, it was found that the lack of integrative curriculum standards and inefficiencies in communal facility logistics are the main determinants that guarantee the quality of sleep hygiene in dormitories. The results of the analysis recommend the need for policy reforms that include reducing overlapping materials, implementing staggered scheduling to minimize queues, and standardizing a minimum sleep time of seven hours integrated into Islamic boarding school regulations.